ANALISIS KUANTITATIF PENERAPAN 8 DIMENSI PROFIL LULUSAN PESERTA DIDIK GUGUS SULTAN THAHA 2 - Tri Nabila Azzahra; Destrinelli; Silvina Noviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the quantitative aspects of the implementation of the 8 dimensions of the graduate profile of Sultan Thaha 2 Group students.. These eight dimensions include faith and piety, citizenship, critical reasoning, creativity, collaboration, independence, physical and mental health, and communication. The research method used was a quantitative descriptive approach. The study subjects consisted of students and teachers at SDN 111/I Muara Bulian and SDN 112/I Muara Bulian. Data collection was conducted through a questionnaire using a five-level Likert scale. Data were analyzed by comparing the obtained scores with the ideal score to determine percentages and achievement categories. The results showed that the implementation of the eight dimensions of the graduate profile of students was in the very high category, with an average percentage of approximately 91%. The dimensions of faith and piety and citizenship had the highest achievement, while the dimensions of critical reasoning, communication, and independence were in the medium category. Furthermore, there are differences in achievement between schools, with SDN 111/I Muara Bulian scoring higher than SDN 112/I Muara Bulian, even though both are in the high to very high categories.